The Effectiveness of Contextual Learning in Financial Mathematics Problem for Senior High School - Kurniawati, Mega (Universitas Negeri Surabaya, 2020)
The purpose of this study was to describe contextual learning about financial math problems for secondary high school students. This study begins with development research of learning tools using the 4-D model of Thiagarajan which consists of defined, designed, developed, and disseminated. The research subjects were students of grade 9 of SMK Prapanca 2 Surabaya. Three classes were randomly selected as a pilot test class, experimental class, and control class. The pilot class and the experimental class used a contextual learning model. While the control class uses a conventional learning model. The results showed that classical learning reached 9.268% of the experimental class students increased by 75% of the maximum score, effective student activity during learning, the ability of teachers to manage effective learning, and student responses to positive learning. While the classical learning completeness for the control class is classified as incomplete because only 78.05% of students exceed 75% of the maximum score. Based on inferential statistical analysis, the conclusions obtained from this study are the learning outcomes of students who take contextual learning better than the learning outcomes of students who take conventional learning.Keywords: Learning Outcomes, Contextual Learning, Financial Mathematics Problems